(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
Interference fit is one of the most common assembly methods in textile machinery, this paper focuses on the interference assembly of hollow shaft and sleeve. The mechanical behaviors of hollow shaft and sleeve were investigated by using the finite element method under interference fit and axial tension load. The effects of interference, hollow degree, axial load, friction coefficient, sleeve thickness on the mechanical property were studied. The results show that there is still an “end effect” of the contact stress and equivalent stress of the sleeve under axial load. Maximum equivalent stress of hollow shaft appears on the inside cylindrical surface under tensile loading. Under axial tensile load, contact stress and the equivalent stress of sleeve increases with the increasing of interference, sleeve thickness, and decreases with the increasing of hollow degree and load. The equivalent stress of hollow shaft increases with the increasing of the four parameters. The friction coefficient has a very small effect on the mechanical property.